Research progress of optoelectronic devices based on diamond materials - Fei, Houzhi; Sang, Dandan; Zou, Liangrui; Ge, Shunhao; Yao, Yu; Fan, Jianchao; Wang, Cong; Wang, Qinglin (Frontiers in Physics, 2023)
Diamond has a variety of unique characteristics, including integrates mechanics, electricity, heat, optics and other excellent properties, so that it is widely focus on the field of high and new technology, especially in the optoelectronic technology. Because diamond has the characteristics of high thermal conductivity, high breakdown field (10 mV/cm), high electron and hole mobility, it has a wide application prospect in high temperature, high power and high frequency photoelectric equipment. The wide bandgap (5.47 eV) makes diamond an ideal material in ultraviolet detectors (UV). Its high carrier mobility and breakdown field strength make it an ideal choice for field emission materials, which are expected to be used in high-power electronic devices in the next few years. At the same time, in addition to high hardness, it also has various of excellent physical properties, such as low coefficient of thermal expansion, low coefficient of friction, high acoustic propagation speed and high optical transmittance, so that it has broad application prospects in many fields such as machining, microelectronic devices, optical windows and surface coatings. In addition, diamond also has a high exciton binding energy (80 meV), which plays an important development in deep ultraviolet and high-energy particle detectors. In this article, the latest progress in the application of diamond-based optoelectronic devices is reviewed. A variety of advanced devices and physical phenomena are considered, for example, sensors, transistors, memory, Light-emitting diode (LEDs), ultraviolet detectors and field emission. This review will provide a new idea to promote the development of photoelectric applications based on diamond structure.